A Genetic Screen in Drosophila To Identify Novel Regulation of Cell Growth by Phosphoinositide Signaling - Janardan, Vishnu (G3 (Bethesda), 2019)
Phosphoinositides are lipid signaling molecules that regulate several conserved sub-cellular processes in eukaryotes, including cell growth. Phosphoinositides are generated by the enzymatic activity of highly specific lipid kinases and phosphatases. For example, the lipid PIP(3), the Class I PI3 kinase that generates it and the phosphatase PTEN that metabolizes it are all established regulators of growth control in metazoans. To identify additional functions for phosphoinositides in growth control, we performed a genetic screen to identify proteins which when depleted result in altered tissue growth. By using RNA-interference mediated depletion coupled with mosaic analysis in developing eyes, we identified and classified additional candidates in the developing Drosophila melanogaster eye that regulate growth either cell autonomously or via cell-cell interactions. We report three genes: Pi3K68D, Vps34 and fwd that are important for growth regulation and suggest that these are likely to act via cell-cell interactions in the developing eye. Our findings define new avenues for the understanding of growth regulation in metazoan tissue development by phosphoinositide metabolizing proteins.